한우 수출을 위한 채끝 등심의 온도와 저장 기간에 따른 품질 변화 평가 - 김문주; Moon-ju Kim; 조영동; Young-dong Cho; 황인호; In-ho Hwang (농업생명환경연구, 2021)
본 연구는 홍콩시장으로 한우 수출 시 발생되는 과도한 드립의 발생, 진공 포장의 풀림이나 기포 발생 등 품질 저하를 방지하기 위한 일환으로 최적의 유통 온도를 설정하기 위해 수행하였다. 현재 수출업체에서 적용하고 있는 포장재를 이용하여 수축 진공 포장하고 각각 1℃와 4℃에서 40일까지 저장 후 품질을 평가하였다. 드립 감량, 지방산화도와 적색도의 저하가 4℃에 저장된 시료에서 훨씬 높게 관찰되었으며 이로 인해 4℃의 유통기간은 21일이 적정한 수준으로 사료되며, 반면에 1℃에 저장된 시료의 모든 품질 특성은 40일까지 양호하게 나타나 수축 진공 필름으로 포장 후 1℃의 온도가 유지된다면 선박을 이용한 수출도 가능할 것으로 사료된다. 따라서 본 연구 결과, 유통과정 전반에 걸쳐 1℃의 냉장 온도를 유지하는 것이 품질의 저하를 막을 수 있으며 이를 위해서는 도축 후부터 홍콩에 도착할 때까지 수출전용 냉장 컨테이너에 보관되어 온도가 일정하게 유지되도록 관리되어야 할 것으로 판단되며, 다양한 상황을 시뮬레이션 할 수 있는 더 많은 연구가 필요한 것으로 사료된다. The current experiment was designed to establish optimal distribution conditions for Hanwoo longissimus lumborum muscle (LL) packaged for a Hong Kong market over 40 days. Eight LL muscles were sampled the day after slaughter from a commercial beef export abattoir located in Seoul. Samples were allocated into a 2 × 4 factorial arrangement (stored at 1℃ or 4℃, and aged for 1, 7, 21, or 40 days) and packaged with a 9-layer commercial shrink film; the objective meat quality was determined at the designated days. Moisture content, drip loss, and lipid oxidation data indicated that storage at 1℃ was significantly (p < 0.05) more stable than storage at 4℃. In contrast, the Warner-Bratzler shear force showed a similar tendency (p < 0.05) of significant reduction during the aging period. The objective meat color assessed by redness (CIE a*) revealed that storage at 1℃ significantly improved (p < 0.05) stage redness up to 40 days, while storage at 4℃ maintained a similar redness. The current data indicate that storage temperature is a prime determinant of meat quality, particularly for beef cut packaged in the long-term exporting market, and suggested that maintenance at 1℃ is recommended compared to that at 4℃. The current study highlights the crucial need for the development of a cold-chain handling manual for exporting beef.